Prevalence of asthmatic smokers: Turkish experience (PASTE Study) - Yildiz, Fusun; Dursun, Adile Berna; Disçi, Rian; Abadoglu, Oznur; Atalay, Figen; Ates, Gungor; Ozge, Cengiz (Blackwell Publishing Ltd, 2014)
Background: Although both asthma and smoking are major health problems worldwide, smokers are often excluded from asthma studies. Objectives: It was aimed to verify the prevalence of asthmatic smokers in Turkey and assess the effects of smoking based on clinical parameters, exacerbations and hospitalizations because of lack of national data about the prevalence of smoking among asthmatics. Methods: The study protocol was comprised of a retrospective questionnaire. The asthmatic patients were followed in the outpatient clinics of 18 tertiary hospitals selected from seven different geographical regions in Turkey. We evaluated demographic data, smoking habits, asthma-related diseases, respiratory function and emergency visits. Results: The study population included 1385 patients (M/F: 343/1042), and the mean age was 45.1±14.0 years. Current and former smoking prevalence was 11.4% and 15.1%, respectively. Smoker rates were higher in males and younger asthmatics compared with females and older asthmatics (P<0.01 and P<0.05, respectively). Smoking history ranged from 0.20 to 90 pack-years (the mean was 12.9), and smokers had a higher level of education compared with nonsmokers (P<0.01). Socioeconomically, the most developed region had the highest rate of smoker asthmatics (33.9%; P=0.014). There was an increase in the number of exacerbations in smoker asthmatics during the previous year, but it was not statistically significant (P>0.05). Conclusion: We showed that the smoking prevalence in Turkey was lower in asthmatics (11.4%) compared with the general population (44.5%). Nevertheless, every effort should be made to encourage asthmatics to stop smoking because smoking is a modifiable risk factor for adverse asthma health outcomes. © 2013 John Wiley and Sons Ltd.
Keywords: Asthma; Asthma control; Exacerbation; Prevalence; Smoking; Spirometry; Turkey